Western origins of non-western authoritarianism - Md. , Moniruzzaman (2015)
Authoritarianism in its various forms has been a political reality in many of the countries in Asia, Africa and Latin America since the end of colonialism. Many of these countries experienced repeated emergence of authoritarian regimes, while some experienced their prolonged presence. The authoritarian regimes have always legitimized their stay in power with certain national interests and sought popular legitimacy from the people through various means. In many cases, the authoritarian regimes came to power through military coups, and subsequently civilianized. Academic literatures usually analyze authoritarianism in these countries mainly as a domestic phenomenon. But is it so? This research argues that the non-Western authoritarianism actually has had its origins in the Western countries. Analyzing the emergence and persistence of about 30 regimes of non-Western countries and the characteristics of their foreign relations with major powers in the West namely the USA, Soviet Union (earlier), the UK and France during the past century this research argues that authoritarianism in these non-Western countries have generally been caused by direct or indirect support by the Western countries. In testing this assumption, the research examines three variables namely- evidence whether the regimes came to power through direct West-staged military coup engineered by foreign intelligence agencies; whether the locally emerged authoritarian regimes enjoyed economic and military support by the West; and the general attitudes of the West towards these regimes. The research argues that if these regimes are directly or indirectly supported by the West then we take it that the emergence and institutional survival of the regimes had Western origins.